Relationship Between Body Composition Components and Functional State of the Autonomic Nervous System in Primary School Children with Overweight - Petrik Kyu, Kostenchak-Svystak Oe, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Obesity and overweight in children is a socio-economic and medical problem around the world. [1] Target organs for the influence of excess fat are the heart, blood vessels, kidneys, liver and others. Therefore, more and more scientists and health professionals try to detect, prevent and control childhood obesity. [2] Methods: 72 children aged 10-11 years were examined by body composition parameters using the bioimpedance method on Tanita BC-601 analyzer scales. Heart rate variability and autonomic nervous system status were assessed using a “CardioLab” electrocardiograph. Results: Both BMI and total body fat, visceral fat and fat free mass were statistically significantly correlated with the activity of the sympathetic and parasympathetic systems. As the total fat content of the body increased, the total power of the regulatory systems decreased. Visceral fat content was statistically significantly affected by both ANS systems, but there was a stronger association between visceral fat and the sympathetic nervous system. Conclusion: The data obtained can serve as an impetus for the identification of children with autonomic dysfunction and overweight to develop corrective and preventive programs for the prevention of CVD by normalizing the body composition.